Adsorption of ammonia nitrogen in aqueous solution by the acid activated water treatment sludge. (2016) - Xiong, Shuiying; Qiu, Muqing; Wang, Gusheng
The ammonia nitrogen in aqueous solution can contribute to the eutrophication of water bodies, depletion of dissolved oxygen and toxicity to fish and other aquatic organisms. The removal of ammonia nitrogen in aqueous solution was carried out with many kinds of methods. In this research, the potential and effectiveness of the water treatment sludge was studied as the alternative adsorbents for the removal of ammonia nitrogen in aqueous solution. The water treatment sludge was activated by acid solution. Then, the effects of temperature, contact time and initial ammonia nitrogen concentration on ammonia nitrogen adsorption by the acid activated water treatment sludge were investigated. The results showed that the acid activated water treatment sludge contains porous structures and high surface area. The equilibrium data fitted with the Langmuir isotherm. The adsorption data fitted the pseudo-second-order model much better with R 2 greater than the pseudo-first-order model. The values of ΔH ° and ΔS ° were -34.28 kJ/mol and -113.09 J/mol, respectively. The value ΔG ° of was 0.41 kJ/mol at 308 K.